Assessing the Influence of Environmental Sources on the Gut Mycobiome of Tibetan Macaques - Sun, Binghua; Xia, Yingna; Davison, Samuel; Gomez, Andres; Garber, Paul A.; Amato, Katherine R.; Xu, Xiaojuan; Xia, Dong-po; Wang, Xi; Li, Jin-hua (Frontiers in Microbiology, 2021)
The distribution and availability of microbes in the environment has an important effect on the composition of the gut microbiome of wild vertebrates. However, our current knowledge of gut-environmental interactions is based principally on data from the host bacterial microbiome, rather than on links that establish how and where hosts acquire their gut mycobiome. This complex interaction needs to be clarified. Here, we explored the relationship between the gut fungal communities of Tibetan macaques (Macaca thibetana) and the presence of environmental (plant and soil) fungi at two study sites using the fungal internal transcribed spacer (ITS) and next generation sequencing. Our findings demonstrate that the gut, plant and soil fungal communities in their natural habitat were distinct. We found that at both study sites, the core abundant taxa and ASVs (Amplicon Sequence Variants) of Tibetan macaques’ gut mycobiome were present in environmental samples (plant, soil or both). However, the majority of these fungi were characterized by a relatively low abundance in the environment. This pattern implies that the ecology of the gut may select for diverse but rare environmental fungi. Moreover, our data indicates that the gut mycobiome of Tibetan macaques was more similar to the mycobiome of their plant diet than that present in the soil. For example, we found three abundant ASVs (Didymella rosea, Cercospora and Cladosporium) that were present in the gut and on plants, but not in the soil. Our results highlight a relationship between the gut mycobiome of wild primates and environmental fungi, with plants diets possibly contributing more to seeding the macaque's gut mycobiome than soil fungi.